WY-14,643-mediated promotion of hepatocarcinogenesis in connexin32-wild-type and connexin32-null mice - Moennikes, Oliver; Bannasch, Peter (Carcinogenesis, 2003)
Abstract. Connexin32 (Cx32) is the major gap junction forming protein in liver and lack of functional Cx32 enhances hepatocarcinogenesis. Many tumour-promotin